A paisagem em Ulysses : uma análise fenomenológica do romance de James Joyce - Muliterno, Michele (2021)
Ulysses, by James Joyce, is one of the greatest masterpieces of world literature. Written at the beginning of the 20th century, it is a revolutionary milestone in the history of the novel as a genre. Basically we have the story of Leopold Bloom, tormented by the knowledge that his wife is going to cheat on him that afternoon, wanders through the city of Dublin trying to get home as late as possible. This Leopold Bloom is the one who takes the reader through this landscape, created from the way he perceives the environment that surrounds him. The way he is perceived within this landscape is also presented. It is from this perspective that this thesis seeks to analyze the work, looking for how the landscape is perceived and represented in the work. Michel Collot's studies on landscape, which are based on Merleau Ponty's phenomenology, were the theory used for this analysis. The phenomenology of Jean Paul Sartre and the studies on the relationship between character and author of Mikhail Bakhtin are also used to complement the theoretical foundation of this study. The analysis were done by dividing the 18 chapters of the work into three parts, where the first corresponds to Stephen Dedalus' landscape, the second corresponds to Bloom's landscape, and the last one closes Bloom's landscape and presents us Molly's landscape. In each chapter were observed and described the way the character perceived the landscape (or is perceived in it), its relations with the environment and the others that form it and the landscape horizon.